Acute Rheumatic Fever: Where Do We Stand? An Epidemiological Study in Northern Italy - Marino, Achille; Cimaz, Rolando; Pelagatti, Maria Antonietta; Tattesi, Giulia; Biondi, Andrea; Menni, Laura; Sala, Marco; Calzi, Patrizia; Morandi, Francesco; Cortinovis, Francesca; Cogliardi, Anna; Addis, Claudia; et al. (Frontiers in Medicine, 2021)
Acute rheumatic fever (ARF) is a non-septic complication of group A β-hemolytic streptococcal (GAS) throat infection. Since 1944, ARF diagnosis relies on the Jones criteria, which were periodically revised. The 2015 revision of Jones criteria underlines the importance of knowing the epidemiological status of its own region with updated data. This study aims to describe ARF features in a retrospective cohort retrieved over a 10 year timespan (2009-2018), and to report the annual incidence of ARF among children in the Province of Monza-Brianza, Lombardy, Italy during the same period. This is a multicentric cross-sectional/retrospective study; 70 patients (39 boys) were diagnosed with ARF. The median age at diagnosis was 8.5 years (range 4-14.2 years). Overall, carditis represented the most reported major Jones criteria followed by arthritis and chorea (40, 27, 20 cases, respectively). In order to calculate the annual incidence of ARF, only children resident in the Province of Monza-Brianza were included in this part of the analysis. Therefore, 47 patients aged between 5 and 14 years were identified. The median incidence during the study time was 5.7/100000 (range 2.8-8.3/100000). In the Province of Monza-Brianza we found an incidence rate of ARF among children aged 5-14 years constantly above the threshold of low-risk area as defined in the 2015 revision of Jones criteria. Therefore, the diagnosis of ARF should be based on the moderate-high risk set of Jones criteria. However, given the burden of secondary prophylaxis, expert opinion is advisable when the diagnosis of ARF is uncertain.